Enhanced performance and stability of electrochromic device based on poly (3-methylthiophene) using 2-thiophenecarboxylic acid as interfacial modifier. (November 2018) - Zhang, Wenzhi; Zhang, Ge; Chen, Xianghong; Wang, Sumin; Wang, Yan; Zhu, Shengbo; Wang, Qiguan
Graphical abstract: Poly (3-methylthiophene) covalently bonded to ITO electrode modified with 2-thiophenecarboxylic acid was synthesized and employed in the fabrication of high-performance polymer electrochromic device. Highlights: The PMeT film covalently bonded to ITO electrode was prepared using ThCA as modifier. The adsorption force between the PMeT film and ITO electrode was enhanced. The ECD based on PMeT-ITO exhibited better electrochromic stability. Abstract: In this paper, we modified the surface of Indium tin oxide (ITO) electrode with 2-thiophenecarboxylic acid (ThCA), and then prepared the poly (3-methylthiophene) (PMeT) film covalently bonded to ITO electrode (PMeT-ITO) by electrochemical polymerization. It was found that interfacial modification enhanced the adsorption force between PMeT and ITO substrate, PMeT-ITO exhibited better stability. Moreover, we successfully fabricated the electrochromic device (ECD) by using PMeT films on ITO substrate. The results of cycling tests showed that the optical contrast of ECD based on PMeT-ITO was kept almost the same after recycling 66 times. Compared with ECD based on PMeT physically adsorbed on bare ITO substrate (PD-PMeT), the ECD based on PMeT-ITO possessed good electrochromic stability in the 150 cycles. This demonstrated that the interaction between PMeT and ITO substrate became stronger by chemical bonding approach, improving the cyclic stability of ECD.